Distribution of SARS-CoV-2 Variants in West Java Based on Genomic Surveillance Data, 2021-2022 - Cut Nur Cinthia Alamanda; Ida Parwati; Gusti Ayu Prani Pradani; Azzania Fibriani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Coronavirus Disease 19 (COVID-19), the disease caused by SARS-CoV-2, was declared a pandemic in early 2020. With the emergence of different strains of SARS-CoV-2 mutations, efforts to reduce infection rates and help vulnerable populations remain in question. Genomic surveillance has been carried out on COVID-19 cases to detect new variants and monitor trends in circulating variants. Genomic surveillance is important because it can detect virus characteristics, estimate the prevalence of specific variants in the community, assess the extent to which medication can combat the variants, and analyze virus transmission in outbreaks. The purpose of this study was to investigate the prevalence of SARS-CoV-2 genomic variants in West Java and to inform policymakers in developing strategies to reduce the transmission rate of the SARS-CoV-2 virus. According to the inclusion criteria, variant sequence data were acquired from Global Initiative on Sharing All Influenza Data (GISAID) for the period January 1st, 2021-December 31st, 2022 and evaluated cross-sectional descriptively. This data were obtained from West Java. The majority of the samples came from Bandung Regency, where the Delta (AY), BA1 and BA5 variations predominated. The dynamic of the SARS-CoV-2 cases was influenced by government policies such as imposition of the restriction on community activities and public holiday. Because SARS-CoV-2 is subject to mutations, the various varieties must still be monitored to determine the influence on society. In the future, surveillance for any microorganisms with the potential to cause epidemics is urgently needed in order to mitigate the spread of the disease.